Implementasi Priority Packet Scheduling di Sisi Node Pengirim pada Mobile Ad-hoc Network berdasarkan Ukuran Paket Data - Muhammad Ichwan Pradana; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Mobile Ad-hoc Network (MANET) is a mobile network, due to its nature MANET has basic weaknesses in its reliability when traffic is high. High network traffic is caused by one of the factors including the size of the packets being transmitted, which can cause smaller packets to be susceptible to not reaching the recipient or packet loss. Packet Scheduling is one solution to address these issues. This research uses Priority Packet Scheduling method based on the size of the data packet. Data packets with a size greater than 1000 bytes will be given high priority and sent first. Packets with a size between 1000 bytes and 500 bytes will be given medium priority and packets below 500 bytes will be given the lowest priority. Each priority will still receive a sending quota to prevent starvation. The results of Priority Packet Scheduling show that the method does not have an impact on the Packet Delivery Ratio and even experienced an increase in Average End-to-End Delay when compared to not using Priority Packet Scheduling. However, the Average Throughput values obtained with this method are significant.